THE CORRELATION BETWEEN PARENT KNOWLEDGE AND INJURY PREVENTION PRACTICES ON UNDER-FIVES - intan mutiara putri (Universitas Muhammadiyah Mataram, 2019)
Abstract: Injury is still one of the problems that need special attention because high mortality rate caused by injuries is still quite high. According to report of World Health Organization (WHO), from 5.8 million deaths worldwide, more than 3 million deaths among them occurred in developing countries due to the incidence of injuries. By analyzing the characteristics of the development, toddlers are more at risk of injury than adults. Injury results in 42% of deaths in children aged 1-4 years in the United States. Knowledge about the risk of injury and the practice of its prevention as well as handling is needed to parents who have under-fives children, so they can provide appropriate action. The purpose of this study was to determine the correlation between the level of knowledge and the practice of injury prevention in under-five children in Bangunjiwo Kasihan Bantul Yogyakarta. This study used a descriptive observational method with a cross sectional approach with a quantitative approach. The sampling technique applied the cluster random sampling method obtained by Anggrek Bulan Maternal Care at Kalangan Village. The numbers of samples were 90 under-five children. Bivariate statistical analysis employed Chi Square test. The results of the statistical test showed that there was a correlation between the level of knowledge and the practice of injury prevention in under-five children in Bangunjiwo Kasihan Bantul, Yogyakarta (p-value = 0.016). Thus, midwives need to improve health counseling for parents who have under-five children about the risk of injury to children, so parents have good knowledge regarding children's health, especially regarding the risk of injuries that can occur to children.